Economic analysis of sugammadex versus neostigmine for reversal of neuromuscular blockade for laparoscopic surgery in China - Maodong Ren; Ying Wang; Yan Luo; Jia Fang; Yongji Lu; Jianwei Xuan (Health Economics Review, 2020)
Background: Neuromuscular blockade and pneumoperitoneum (PP) are important factors to ensure successful laparoscopic surgery. However, residual neuromuscular blockade (rNMB) and PP are associated with many unfavorable complications. The aim of this study is to compare the cost-effectiveness of using sugammadex versus neostigmine in laparoscopic surgery in China. Methods: A decision tree model was developed with a time horizon based on laparoscopic surgery related hospitalization duration. 2000 patients using sugammadex or neostigmine were simulated within the model. The model outcomes included incidence of rNMB and PP related complications and their treatment costs. Data on clinical efficacy, safety and cost were collected from published literature and interviews of physicians. Results: The model projected that treatment with sugammadex instead of neostigmine would lead to 673 fewer total complications, including rNMB/PP related complications, hospitalization, and other AEs (621 events versus 1294 events, respectively). Use of sugammadex was associated with an incremental medication cost of 1,360,410. However, 93.6% of the increased medication cost can be off-set by the reduced costs attributable to treatment of rNMB related complications, PP related complications, hospitalization and other adverse events in sugammadex group. In aggregate, the sugammadex group incurred an incremental cost of 86,610 to prevent 673 complications, (128.56 per one rNMB/ PP related complications prevention). One-way sensitivity analysis confirmed the robustness of the model. Conclusions: Use of sugammadex in replacement of neostigmine would result in significantly lower rNMB/PP related complications but at a substantially higher medication cost. Upon accounting for the costs associated with treatment of rNMB/PP related complications, 93.6% of medication cost is projected to be offset. In balance, sugammadex appears to offer good value for reversal of neuromuscular blockade for laparoscopic surgery in China.
Keywords: 330; Sugammadex; Neostigmine; Residual neuromuscular blockade; Economic analysis